Socio-economic and geographical factors of development - study case: cities Berana, Andrijevice and Plava - Rajović, Goran; Bulatović , Jelisavka (Journal for Geography, 2012)
The paper analyzes the socio-economic and geographic factors for Berane Andrijevice and Plava. The above urban settlements are located in the northeastern part of Montenegro. Isolated traffic and geographical position adversely affects the economic and social development of urban settlements. For the development of cities of greater importance are the geo-morphological and hydrological characteristics of the terrain, the climate and geology, which limits greatly compensates for modern construction techniques. Berane population increased in the period 1948-2003 to 26.81%, while in Andrijevica decreased by 42.48% and 12.43% of Plav. These data suggest to us most vividly, what are the demographic changes occurring in the region. Age groups, due to migration and decreasing birth rate changes and gets unfavorable features - reducing the proportion of younger and older increases the proportion of the population. In both cases, the disturbed age structure has a reverse effect on the movement of the population (the size of reproductive contingent), but also to all other structures of the population (the size of contingent employment, population, compulsory school contingent, contingent dependent population ratio).The main characteristic of modern urban development of cities provide processes of industrialization and urbanization. However, the economic crisis in Montenegro at the beginning of the nineties due to isolation, the economic and social strategy of circling and lack of long term economic development, stopped the social, economic, technical and technological development of urban settlement Berane, Andrijevica and Plav.